2020
DOI: 10.1016/j.scitotenv.2020.140123
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID-19 induced lockdown measures on maritime settings of a coastal region

Abstract: The spread of coronavirus (COVID-19) caused an unprecedented implementation of lockdown measures across world's nations. Veneto Region, located in NorthEastern Adriatic Sea was one of the first maritime regions in Italy and Europe subjected to progressive lockdown restrictions. We systematically analyse the effects of national lockdown policies on maritime settings of the region using Automated Identification System (AIS) data from fishing vessels, passenger ships, tanker and cargo vessels collected through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 27 publications
3
70
0
Order By: Relevance
“…Personal and elective international and domestic air travel was either terminated or restricted to repatriation ights [60,61] with ow-on e ects to the tourism industry [61,62] and the communities and conservation organisations that rely on tourism income [63]. The associated reduction in air cargo volume [64], as well as overall shipping [65,66] resulted in disruptions to global as well as national supply chains, not only of manufacturing parts [67] and health care materiel [68,69], but also of food production [70,71] and food distribution [72,73], which in part was fuelled by panic buying [61]. In consequence, COVID-19 acted as a disruptor a ecting labour markets, in particular expatriate workers [74,75], with cascading e ects on remittances [76], and thus local economies in countries of origin [77].…”
Section: Covid-19 As a Cross-sectorial Disruptormentioning
confidence: 99%
“…Personal and elective international and domestic air travel was either terminated or restricted to repatriation ights [60,61] with ow-on e ects to the tourism industry [61,62] and the communities and conservation organisations that rely on tourism income [63]. The associated reduction in air cargo volume [64], as well as overall shipping [65,66] resulted in disruptions to global as well as national supply chains, not only of manufacturing parts [67] and health care materiel [68,69], but also of food production [70,71] and food distribution [72,73], which in part was fuelled by panic buying [61]. In consequence, COVID-19 acted as a disruptor a ecting labour markets, in particular expatriate workers [74,75], with cascading e ects on remittances [76], and thus local economies in countries of origin [77].…”
Section: Covid-19 As a Cross-sectorial Disruptormentioning
confidence: 99%
“…In particular, the behaviour of human activities in the ocean have been radically altered by the COVID-19 pandemic, with port restrictions and changes in consumption patterns impacting multiple maritime sectors, most notably fisheries, passenger ferries and cruise ships [7][8][9][10] ; sectors which rely heavily on the movement of people and goods. As with previous economic recessions 11,12 , changes in vessel movement associated with COVID-19 are also likely to result in significant short-and long-term effects on multiple anthropogenic pressures, such air pollution [12][13][14][15] , the spread of invasive alien species 16,17 , or collisions with marine animals 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Localised studies have already reported reductions in underwater noise 20 , water turbidity 21 and fishing effort 8 as a result of the reduction of the vessel activity during the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…increased wildlife poaching, destructive fishing, plastic pollution) [3][4][5]. In the ocean, the blue economy, a rapidly growing ocean-based economic sector that includes tourism, fisheries, biotechnology, aquaculture, renewable energy, and other sustainable uses [6], has been significantly impacted with tourism and maritime transport greatly decreased on multiple scales [7,8]. Additionally, reduced demand for fisheries products, combined with COVID-19 outbreaks among seafood workers, has led to some large reductions in commercial and small-scale fishing activity and increased recreational fishing in some areas [9,10].…”
Section: Introductionmentioning
confidence: 99%